Peningkatan Perilaku PSK Menggunakan Buku Saku Dalam Pencegahan Dan Penanganan Penyakit Menular/ HIV Di Gunung Kemukus Kabupaten Sragen - Suyanto Suyanto; Dwi Susi Haryati (Interest : Jurnal Ilmu Kesehatan, 2017)
Abstract: Pocket Books, PSK, Mount Kemukus. Some of the main reasons Woman Being prostitution as well as economic factors. To PSK is a choice that has a lot of risk one is contracting sexually transmitted diseases/ HIV and they have a big share in the spread of the disease. Thus there is no reason the prostitutes must have behaviors that can prevent and make the handling of infectious diseases/ HIV as a result the risk of becoming prostitutes. But until now they have not done well with their proven PSK contract some sexually transmitted diseases.Given the rise of the behavior before and after using a pocket book in the prevention and treatment of sexually transmitted diseases/ HIV PSK Mount Kemukus Sragen. This study was a quasi-experimental, using a pre-post test approach using a questionnaire. Enelitian population are the prostitutes in Mount Kemukus Sragen with samplel number as many as 30 people. Furthermore, the analysis using quadratic Kai Test (Chi Square) with the aid of a computer. The results showed that the behavior of infectious disease prevention / HIVsebelum and after given pocket book while there is no difference to the behavior of the handling of infectious diseases/ HIV there are significant differences. Based on these results the researchers advised to maintain good handling practices already and do efforts to improve prevention behaviors.